Effect of selected plant growth regulators and abiotic factors on micropropagation of plantlets from shoot bud cultures of boesenbergia rotunda (l.) mansf: a valuable medicinal plants / Nor Azma Yusuf, Shamsiah Abdullah and Asmah Awal - Yusuf, Nor Azma; Abdullah, Shamsiah; Awal, Asmah (Research Management Institute (RMI), 2013)
Boesenbergia rotunda is a herbaceous plant belonging to family Zingiberaceae and the pharmacological importance of this plant is mainly due to the presence of flavanoids, essential oil and chalcones (Jaipetch et al., 1982; Pandji et al., 1993; Trakoontivakorn et al., 2001). Recently, 4-hydroxypanduratin A and panduratin A, which isolated from the rhizome of B. rotunda were found to show high inhibitory activity towards dengue-2 virus protease at 120 ppm (Tan et al., 2006). Conventionally Boesenbergia rotunda is propagated by dividing into small clumps and planted in the soil, however this process regularly results in fungal diseases that can control the quality of medicinal values of the plants. In view of the problem of the fungal diseases in the field, in vitro culture technique can be a wonderful alternative technique for mass propagation of disease free plant material for B. rotunda. In vitro propagation of the Zingiberaceae family has already been reported, for example Alpinia galanga (Inden & Asahira 1988) and Zingiber officinale (Hosoki & Sagawa 1977; Pillai & Kumar 1982; Inden & Asahira 1988; Bhagyalakshmi & Singh 1988; Ikeda & Tanabe 1989).However, to date there are scarce report on the rapid micropropagation of B. rotunda, which will be discover in this study. The aim of study is to establish a micropropagation protocol that can be applied to B. Rotunda by focusing at the effect of selected plant growth regulators (BAP, Zeatin, 2,4-D and IAA) and effect of divided or undivided shoot buds on proliferation rate of this species. The shoot explants of the in vitro plantlets were cultured in solid medium supplemented with selected plant growth regulators. Shoot bud will be cut into half and subculture for 3 times to observe the effect of the undivided and divided shoots on proliferation rate of the B. rotunda. An average of shoots produce from the experiment will be analysed using student t test.